DYNAMICS OF SLEEP-WAKE CYCLICITY ACROSS THE FETAL PERIOD IN SHEEP (Ovis aries) - Karlsson, ÆK. (2011)
All adult mammals examined thus far exhibit sleep bout durations that follow an exponential distribution and wake bout durations that follow a power-law distribution. In altricial rodents such as rats and mice, exponential distributions of sleep bouts are found soon after birth, but the power-law distribution of wake bouts does not emerge until the third postnatal week. Also, both sleep and bouts consolidate across the early postnatal period. It is not known whether similar developmental processes occur in precocial species during the prenatal period. Here we characterize sleep-wake development in a precocial species, the domestic sheep (Ovis aries), from 114–148 days gestational age (DGA). Sleep and wake bout durations exhibited exponential distributions throughout the fetal period with some evidence of an emerging exponential-to-power-law transition for wake bouts toward the end of gestation. Both sleep and wake bouts consolidated in an orderly fashion across development and there was little evidence of circadian variation, even in the oldest subjects. These results indicate that similar patterns of sleep-wake organization are found prenatally in a precocial species as are found postnatally in altricial species. Data from more species are needed to fully realize the benefits of a developmental comparative approach for understanding the forces that have shaped the ontogeny and phylogeny of mammalian sleep.